Chapter Парадоксальность как специфика художественного творчества Ф.М. Достоевского: приемы, стилемы, воздействие - Kotelnikov, Vladimir (Biblioteca di Studi Slavistici, 2023)
Paradoxality as a Specific Feature of Dostoevsky's Literary Works. Techniques, Stylistics, Mechanisms of Action. All works by Dostoevsky reveal the presence of paradox. These paradoxes act according to mechanisms that depend either on the fictional (polyphonic) or nonfictional (monologic) text "dominant." Taking as a starting point (a) the arguments of G.S. Morson, according to whom paradoxes "seem to carry the quintessence of 'Dostoevskyism', particularly of his brand of humor," (b) the analysis of Dostoevsky's paradoxical humor; and (c) the three main categories of paradoxes ("empty or rhetorical", "negative", "positive"), we argue that Dostoevsky applies a fourth type of paradox, one that affects neither the premise nor the ending of the paradoxical structure, but their intrinsic logical interconnection. This article analyses a repertoire of paradoxical techniques used by Dostoevsky, focusing on the destabilizing humoristic function they enact.